Curcumin Nanoformulations for Colorectal Cancer: A Review - Wong, Kar En; Ngai, Siew Ching; Chan, Kok-Gan; Lee, Learn-Han; Goh, Bey-Hing; Chuah, Lay-Hong (Frontiers in Pharmacology, 2019)
Colorectal cancer (CRC) is the third most deadly and prevalent form of cancer, after lung cancer and liver cancer. Over the years, natural compounds have been explored as an alternative to conventional therapies for cancer which include surgery, radiotherapy and chemotherapy. Curcumin, an active constituent of turmeric has been associated with various health benefits. It has gained much attention as an anticancer agent due to its ability to regulate multiple cell signalling pathways including NF-κB and STAT3 that is crucial in cancer development and progression. Nevertheless, the clinical application of curcumin is greatly restricted because of the low water solubility, poor oral absorption and rapid metabolism. These issues have led to the development of curcumin nanoformulations to overcome the limitations of pure curcumin. Nanotechnology-based delivery systems have been widely used in the formulation of poorly-water soluble drugs. Besides, it could also provide additional benefits of cellular targeting as well as improvement in cellular uptake. To be a desirable therapeutic agent, these nanoformulations should display a greater anticancer activity compared to free curcumin and non-toxic to the normal cells. This review highlights the design and development of various nanotechnology approaches to deliver curcumin for use in CRC such as liposomes, micelles, polymer nanoparticles, nanogels, cyclodextrin complexes, solid lipid nanoparticles and gold nanoparticles. Nanoformulations of curcumin have been shown to be a beneficial approach in overcoming the limitations of curcumin in drug delivery context for the management of colorectal cancer.